Investigating the Strength Against Fire and Microstructure of Ultra-High-Performance Concrete - Muhammad Haseeb Zaheer; Murad Khan; Adnan Khan; Hamayun Khan Kakar; Zohaib Ullah (Journal of ICT, Design, Engineering and Technological Science, 2022)
This study aims to produce Ultra-High-Performance Concrete utilizing locally available material. The experimental study includes silica fume with rice husk ash in combination with steel fibers. Various trials were made using different volumes of local materials and steel fibers to produce UHPC. Different properties were evaluated, such as compressive strength, tensile strength, and Scanning Electron Microscopy (SEM). Results show that UHPC can be produced using locally available materials as both the properties were examined with and without heating at higher temperatures and providing satisfactory strength. SEM tests were also performed to evaluate the microstructural study of the ultrahigh-performance concrete. SEM observations discovered that the transition zone between fine aggregates and the cement paste is improved by using silica.